INOVASI PLETEK IKAN RASAU SEBAGAI UPAYA PEMBERDAYAAN SUMBER DAYA LOKAL DI DESA SUAK LANJUT - Nur Fitriana; Abdu Syukur Amin; Ade Rahma Sagala; Dea Wulan Dari; Dhea Mustika; Dimas Turahman; Indah Ramadhany; Muhammad Zaky Hilmy; Mutiara Sukmita; Nanda Saputra; Siti Raiyan Nur Fadilah; Yunita Lumban Raja (LPPI UMN AL WASHLIYAH, 2026)
The Muhammadiyah Aisyiyah Community Service Program (KKN MAs) Group 9 in Suak Lanjut Village, Siak Regency, focused on utilizing the local potential of rasau fish (Hampala macrolepidota), which has long been overlooked by the community due to its fine bones and bland taste. Using a Participatory Action Research (PAR) approach, the program was implemented through several stages: problem identification, community education, and demonstrations on processing rasau fish into an innovative snack called Pletek. The program involved women from the PKK (Family Welfare Movement) as the primary participants through outreach sessions, hands-on training, and the distribution of recipe booklets. The results of the activity demonstrated high levels of community enthusiasm and participation, reflected in interactive discussions and the participants’ desire to develop Pletek as a product with economic value. Tangible outputs—including the processed Pletek product and the recipe booklet—serve as tools for ongoing learning. This program has proven effective in enhancing the community’s knowledge, skills, and collective awareness regarding the use of rasau fish as a local food source, while also opening opportunities for the development of MSME-based businesses.